Findings from a pilot study of buprenorphine population pharmacokinetics: A potential effect of HIV on buprenorphine bioavailability. (1st December 2022) - Bart, Gavin; Jaber, Mutaz; Giang, Le Minh; Brundage, Richard C.; Korthuis, P. Todd
Abstract: Background: Buprenorphine is widely used in the treatment of opioid use disorder (OUD). There are few pharmacokinetic models of buprenorphine across diverse populations. Population pharmacokinetics (POPPK) allows for covariates to be included in pharmacokinetic studies, thereby opening the potential to evaluate the effect of comorbidities, medications, and other factors on buprenorphine pharmacokinetics. This pilot study used POPPK to explore buprenorphine pharmacokinetics in patients with and without HIV receiving buprenorphine for OUD. Methods: Plasma buprenorphine levels were measured in 54 patients receiving buprenorphine for OUD just prior to and 2–5 h following regular buprenorphine dosing. A linear one-compartment POPPK model with first-order estimation was used to evaluate buprenorphine clearance (CL/F) and volume of distribution (V/F). Covariates included weight and HIV status. Results: All HIV+ patients reported complete past-month adherence to taking antiretroviral therapy that included either efavirenz or nevirapine. Buprenorphine CL/F was 76% higher in HIV+ patients (n = 17) than HIV- patients (n = 37). Buprenorphine V/F was 41% higher in the HIV+ patients. Conclusions: POPPK can be used to model buprenorphine pharmacokinetics in a real-world clinical population. While interactions between ART and buprenorphine alter buprenorphine CL/F, we also found alteration in V/F. Proportionate changes in CL/F and V/F might indicate a primary effect on bioavailability (F) rather than two separate effects. These findings indicate reduced buprenorphine bioavailability in patients with HIV. Highlights: Buprenorphine pharmacokinetics can be modeled in a clinical population. Buprenorphine CL/F is 76% greater in those with HIV on antiretroviral therapy. Buprenorphine V/F is 41% greater in those with HIV on antiretroviral therapy. Buprenorphine bioavailability may be reduced in those with HIV.